(untitled) (Journal of the College of Basic Education, 2023)
Industry is the basic base on which countries depend on construction and development, as all types of industries have an effective role in construction and economic development, especially in developing countries. Studying the spatial distribution of economic activity, then analyzing the factors influencing its distribution pattern and the problems it faces are among the priorities of geographical researchers. The problems faced by the floor slabs industry in the study area are addressed and the necessary solutions are developed. The problem of lack of government support has ranked first with a rate of (15.4) among the problems facing the floor slabs industry throughout the study area, while we find that the problem of Poor industrial financing ranked second with a rate of (13.5), the problem of lack of energy and fuel came in third place with a rate of (11.6), and the fourth rank came with the problem of difficulty in obtaining raw materials with a rate of (11.6). The sixth rank, with a percentage of (11.6), while the problem of technology ranked seventh, with a percentage of (9.8), while the problem of work ranked eighth, with a percentage of (7.7), while the problem of marketing ranked ninth, with a percentage of (5.8), while the problem of transportation ranked Ranked last, with a rate of (3.3), and developed the necessary solutions The floor slabs industry occupies an important and prominent position among the various sectors of industries because it helps to: 1- These industries work in the production of building materials that are very important to the lives of citizens through their involvement in building and construction operations. 2- Employ manpower to complete related manufacturing operations such as manufacturing, transportation, etc